Can females choose to avoid mating failure in the seed bug Lygaeus simulans?. (July 2017) - (Ginny) Greenway, E.V.; Balfour, Vicki L.; Shuker, David M.
Abstract : It is becoming increasingly clear that copulation does not necessarily always lead to offspring production in many organisms, despite fertilization success presumably being under both strong natural and sexual selection. In the seed bug Lygaeus simulans, between 40% and 60% of copulations fail to produce offspring, with this 'mating failure' representing a significantly repeatable male-associated trait. Mating has been demonstrated to be costly in this species and, as such, we might expect females to minimize the chance of mating failure by displaying a preference for males with higher insemination success where possible. After assaying males for mating failure, we asked whether females preferred males with a history of successful inseminations versus unsuccessful inseminations in pairwise mate choice trials. Contrary to our expectations, females showed no preference for more successful over less successful males. Moreover, females showed no preference for larger males in the choice trials, even though larger males were significantly more likely to successfully inseminate females in the initial assay. This apparent lack of female precopulatory choice suggests that postcopulatory choice mechanisms may be key to mating failure in this species. However, this does not necessarily explain why females pay the cost of mating with males they will then reject via postcopulatory processes. More generally, our results suggest that mating failure may play a largely underappreciated role in mating systems evolution, influencing both the cost of choosiness, and the costs and benefits of polyandry. Highlights: Failure to produce offspring despite mating is surprisingly common across species. In L. simulans, this mating failure is a repeatable male-associated trait. Here we presented females with a choice between failure-prone and successful males. Females mated randomly with respect to each male's previous mating success. Thus precopulatory choice does not function to minimize reproductive failure.